KEY ACCOUNT MARKETING ANALYSIS WITH MEDIATION ROLE OF SERVICE QUALITY IN OPTIMIZING THE USE OF ELECTRIC ENERGY SOURCES (PLN) - Putu Ayu Titha Paramita Pika (ID Solutions, 2022)
The purpose of this study is to determine and analyze the effect of key account marketing on the Optimization of 35,000 Megawatt of Electricity, also to know and analyze the effect of service quality on the Optimization of 35,000 MW of Electrical Power as well as knowing and analyzing the effect of key accounts marketing on the Optimization of 35,000 MW Electricity Power of PT PLN (Persero) Distribution of Central Java and DIY by mediating the quality of service either partially or simultaneously. This research is descriptive quantitative research with respondents who are used as samples consisting of 75 respondents. Data collection was carried out by distributing questionnaires to obtain responses to the optimization of electrical power carried out by PT PLN (Persero) Distribution of Central Java. The results showed that the effect of key account marketing and the quality of service positively influenced the Optimization of 35,000 MW Electricity PT PLN (Persero) Distribution of Central Java, either partially or simultaneously.